Identification of students' misconceptions in genetic materials using four-tier diagnostic test - Maysyaroh, Ulfi; Noor, Meiry Fadilah (Inornatus: Biology Education Journal, 2025)
Misconceptions are one of the main causes of students’ difficulties in understanding biological concepts, which can affect how they apply biological knowledge in everyday life. Genetics is one of the biology topics that is particularly prone to misconceptions. This study aims to identify misconceptions experienced by public high school students in Brebes Regency during the 2021–2022 academic year on the topic of genetic substance. This research employed a quantitative approach with a descriptive method. The sample consisted of 87 twelfth-grade students from three public high schools in Brebes Regency selected through purposive sampling. Data were collected using a four-tier diagnostic test. The results showed that the level of student misconceptions reached 39.10%. These misconceptions were classified as moderate, with 67.50% identified as pure misconceptions, 14.05% as false positives, and 18.45% as false negatives. The sub-concept with the highest level of misconceptions was Chromosomes, with a percentage of 52.87%. Based on these findings, it can be concluded that public high school students in Brebes still experience misconceptions regarding Genetic Substance. Therefore, remediation efforts by teachers are necessary to help address and correct these misconceptions.